Work relationships: counteracting the negative effects of conflict. Issue 2 (11th April 2016) - Jungst, Martijn; Blumberg, Boris
Abstract : Purpose: Guided by social resource theory, this study aims to examine the influence of conflict (i.e. task and relationship) on performance. The authors investigated whether job engagement mediates this relationship and whether social network quality moderates the relationship between conflict, job engagement and performance. Design/methodology/approach: The authors built and tested a moderated mediation model, using data from 217 graduate students. Findings: Results showed that job engagement operates as a mediating mechanism between task conflict and performance. The authors also found that the indirect effect of job engagement depended upon the quality of the social networks. When the quality of the social network was high, both the task and relationship conflict did not negatively influence the association between job engagement and performance. Research limitations/implications: These findings provide new insights into how social embeddedness in the form of social network quality can create a social context in which conflict works out less detrimental. Practical implications: Given that employees are interdependent and coworkers are likely to differ in their personal values and opinions, the authors conclude that managers should facilitate the development of meaningful relationships at work. Originality/value: Whereas prior research has found conflict (i.e. task and relationship) to negatively associate with performance, the authors show that social networks do affect the strength of the relationship between conflict (i.e. task and relationship) and performance.